Kinematic changes during learning the longswing on high bar - Williams, G.; Irwin, G.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Understanding technique development during complex skill learning provides information that can be used to influence feedback and skill development. The purpose of this study was to investigate changes in longswing technique during an 8 week period of learning. Fourteen male participants with no previous high bar experience took part in the training study. Data were collected using a CODA motion analysis system (200 Hz) during weekly testing sessions. There was a significant increase in swing amplitude for the group between week 1 and all subsequent weeks (p < .05). Based on initial swing amplitude three patterns of learning were displayed; each having distinctive functional phase characteristics. This study highlights the importance of quantifying changes in technique throughout learning on an intra-individual basis, to understand how technique changes.